RASIONALISASI TRADISI BERMAZHAB MENURUT SHAH WALI ALLAH - A Asmawi (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2013)
Shah Wali Allah adalah ulama yang hidup pada masa pra modern abad 17 di India. Seorang tokoh yang mempunyai perhatian yang utuh dalam menyelesaikan problematika umat Islam yang ada di sekitarnya. Salah satu upaya pembaruan yang digagas olehnya adalah usaha untuk mempertemukan berbagai aliran keagamaan yang tumbuh dan berkembang di India. Konsep mazhab oleh Shah Wali Allah adalah hasil dialektika kehidupannya dalam menyelesaikan problematika krisis multidimensi yang dialami oleh umat Islam Indo-Pakistan India. Yaitu adanya deferensiasi antarkelompok keagamaan, tak terkecuali mazhab dalam hukum Islam. Pemikiran ini berusaha memberikan tawaran-tawaran konsep berijtihad, ber-mazhab dan taklid. Pemikiran tentang mazhab yang tertuang dalam kitab al-Ins}a>f fi Asba>b al-Ikhtila>f, walaupun dalam pengelompokan terhadap tahapan-tahapan sejarah lemah, tetapi pemikiran tersebut adalah produk genuine pembaruan hukum Islam dari Shah Wali Allah yang dalam perspektif sosiologis dapat dikategorikan sebagai upaya pemurnian ajaran Islam saat menghadapi krisis dengan solusi rasionalisasi tradisi ber-mazhab. Shah Wali Allah is an theologian who lived in before modern, precisely in 17 century in India. He is a prominent figure who devotes his live to solve Islamic followers problems surround him. One of his efforts is to meet some religion paths which grow up in India. The concept of mazhab proposed by Shah Wali Allah is the result of dialectic of his life in solving multi dimension of crisis experienced by Islamic followers of Indo-Pasistan India. The problem is the emergence of differentiation among group of religion followers, including mazhab in Islamic law. This thinking offers concept of doing ijtihad, mazhab, and taklid. The thinking of mazhab which is presented in book of al-Insaf fi Asbab al-Ikhtilaf, although in grouping the phases of history is weak, however the thinking is genuine product of Shah Wali Allah in renewing Islamic law. This product in sociological perspective can be categorized as an effort to purify Islamic teachings when it is up against crisis with rationalization of tradition in doing mazhab as the Solutions